Beginning your counseling career : graduate preparation and beyond - Adekson, Mary Olufunmilayo (New York, NY : Routledge, 2020)
"Beginning Your Counseling Career is designed for students taking preliminary courses in counseling, as well as practicum and internship classes, at the masters and doctoral levels. It provides a comprehensive overview of the counseling profession and equips students with the clinical and administrative skills they'll need to broaden their focus on professional development. Chapters cover topics rarely covered in counseling texts, including the challenges of starting and completing masters level training, writing etiquette for doctoral students, proposing and completing a dissertation, and more"--
OCLC-licensed vendor bibliographic record.
Keywords: Counseling -- Vocational guidance; Counseling -- Study and teaching (Higher); Counselors -- Training of; PSYCHOLOGY / Psychotherapy / Counseling; PSYCHOLOGY / Mental Health